2014
DOI: 10.1007/s40279-014-0237-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Orthotic Devices in the Treatment of Achilles Tendinopathy: A Systematic Review

Abstract: Orthotic devices such as foot orthoses, splints, taping and bracing are recommended for Achilles tendinopathy (AT). This systematic review was conducted to review the current evidence for the effectiveness of orthotic devices for the treatment of mid-portion or insertional AT. Electronic bibliographic databases (MEDLINE, EMBASE, Current Contents, CINAHL and SPORTDiscus) were searched in May 2014. The methodological quality of included studies was evaluated using the Quality Index. Where possible, effects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 68 publications
2
22
0
1
Order By: Relevance
“…Since the review by Sussmilch-Leitch et al 50 was published in 2012, seven more studies have been published that met the eligibility of this current review. A review by Scott et al 51 concluded that there is ‘weak evidence’ to support the use of foot orthoses, splinting or bracing in managing Achilles tendinopathy. This was in agreement with our review.…”
Section: Discussionmentioning
confidence: 99%
“…Since the review by Sussmilch-Leitch et al 50 was published in 2012, seven more studies have been published that met the eligibility of this current review. A review by Scott et al 51 concluded that there is ‘weak evidence’ to support the use of foot orthoses, splinting or bracing in managing Achilles tendinopathy. This was in agreement with our review.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, heel lifts decrease plantar flexor muscle activity during walking (Akizuki, Gartman, Nisonson, Ben-Avi, & McHugh, 2001; Johanson, Allen, Matsumoto, Ueda, & Wilcher, 2010; Lee, Shieh, Matteliano, & Smiehorowski, 1990), which reduces force on the tendon. Although there is limited evidence supporting its therapeutic use (Carcia, Martin, Houck, Wukich, & Orthopaedic Section of the American Physical Therapy, 2010; Scott, Munteanu, & Menz, 2015), heel lifts are considered a component of standard care for Achilles tendinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…GCS injections are another adjunct that are used in clinics. These injections around the Achilles tendon are controversial because the exact location of the inflammation is rarely found [47]. Moreover, in some cases it is not recommended because of the risk of tendon rupture [48].…”
Section: Discussionmentioning
confidence: 99%